2023
DOI: 10.1002/tpg2.20309
|View full text |Cite
|
Sign up to set email alerts
|

Wheat doubled haploids have a marked prevalence of chromosomal aberrations

Abstract: Double haploid (DH) population development is widely used in many crops, including wheat (Triticum aestivum L.), to rapidly produce fixed germplasm for breeding and genetic studies. The genome shock that takes place during DH induction could induce chromosomal aberrations that can impact genome integrity and subsequently plant fitness and agronomic performance. To evaluate the extent of chromosomal aberrations that exist as a result of the DH process, we studied two wheat DH populations: CDC Stanley×CDC Landma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, our study is the first to report genomic instability in a B. carinata genotype: this was unexpected due to the wider genetic divergence between the Brassica B and C genomes relative to the A and C genomes (Parkin et al 1995, Lagercrantz and Lydiate 1996, Perumal et al 2020). It is possible that this finding relates to the fact that this B. carinata genotype is derived from microspore culture to produce doubled-haploid lines, which may confer genomic instability (Shrestha et al 2023). However, as both B. carinata genotypes used in this study are derived from the same microspore culture process (also at the same time point with the same protocol), there may also be variation for non-homologous chromosome recombination frequency within genotypes of the parent allotetraploid species, as has been hypothesized on the basis of cytological results for B. napus genotypes (Sheidai et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, our study is the first to report genomic instability in a B. carinata genotype: this was unexpected due to the wider genetic divergence between the Brassica B and C genomes relative to the A and C genomes (Parkin et al 1995, Lagercrantz and Lydiate 1996, Perumal et al 2020). It is possible that this finding relates to the fact that this B. carinata genotype is derived from microspore culture to produce doubled-haploid lines, which may confer genomic instability (Shrestha et al 2023). However, as both B. carinata genotypes used in this study are derived from the same microspore culture process (also at the same time point with the same protocol), there may also be variation for non-homologous chromosome recombination frequency within genotypes of the parent allotetraploid species, as has been hypothesized on the basis of cytological results for B. napus genotypes (Sheidai et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Likely, they were caused by colchicine treatment. Shrestha et al [105] studied two wheat DH populations and found many chromosomal aberrations, including duplication, deletion, translocation, and aneuploidy, which were likely caused by unusual chemical exposure during haploid induction and chromosome doubling.…”
Section: Stability Of Doubled Haploidsmentioning
confidence: 99%
“…SHGD and colchicine treatments exert stress on the genome of treated plants. The skim sequencing of wheat (Triticum aestivum L.) showed that various chromosomal aberrations, including deletions, duplications, and aneuploidy, can happen due to genomic shock during DH production [20]. These alterations can affect plant fitness and agronomic performance.…”
Section: Introductionmentioning
confidence: 99%